Anti-predator function of not covering eggs in the initial phase of nesting in Grey Partridge Perdix perdix: a field experiment. Issue 1 (2nd January 2020) - Černý, Martin; Šálek, Miroslav
ABSTRACT : Capsule: An experiment in the field supports the hypothesis that Grey Partridges Perdix perdix purposely expose their first laid eggs in order to test the predation risk at their nest site. Aims: To test the hypothesis that female Grey Partridges leave first laid eggs uncovered to assess the predation risk at their chosen nesting site. Methods: Four area-independent experiments with artificial nests were used. Predation risk was estimated by daily nest failure rate. Generalized linear mixed-effects models were used in statistical analysis. Results: We found that Grey Partridge females could predict nest site safety. At nest sites where the first uncovered egg was depredated, there was a higher predation risk for the whole clutch. Conclusion: Our data statistically support the hypothesis that leaving the first egg uncovered serves to provide a more conspicuous bait for potential predators and could be a female tactic for better recognizing predation risk at a nesting site. Thus, if the first uncovered egg is depredated, the female may start a new clutch elsewhere without wasting investment in the clutch at a site under high predation risk.